Allergy-friendly food for families : 120 gluten-free, dairy-free, nut-free, egg-free, and soy-free recipes everyone will love - O'Brien, Robyn (Andrews McMeel, 2012)
This book is the most trustworthy, comprehensive, practical, and kid-friendly collection of recipes that exists for the important and growing audience of allergy-aware families.